PENDEKATAN MODEL PEMBELAJARAN DISCOVERY DALAM MEWUJUDKAN KEMAMPUAN LITERASI SAINS PADA ANAK USIA DINI - Wahyuseptiana, Yetty Isna (Jurnal AUDI: Jurnal Ilmiah Kajian Ilmu Anak dan Media Informasi PAUD, 2024)
This study aims to determine how important scientific literacy skills are in early childhood. Scientific literacy skills have a role in everyday life so that realizing scientific literacy skills in children can be done through the application of discovery learning models in the learning process. The discovery learning model has a character so that learning that applies the discovery learning model approach is able to build children's curiosity to form knowledge independently. This study uses a qualitative method with the main source is a literature review. The data collection technique used literature study which collected data through books and journals. The data obtained from the literature study were collected and processed by editing, organizing, and finding results. This study in in Kindergarten Al Islam Surakarta. The output of this study is a recommendation regarding the application of the discovery learning model to be able to assist in realizing scientific literacy skills in children. Supported by the importance of scientific literacy skills possessed by early childhood in the 21st century today where every individual is required to have the ability to think critically, think creatively, and one of the skills that need to be possessed is scientific literacy skills.